Collisional scattering of strongly interacting D-band Feshbach molecules in optical lattices - Fansu Wei; Chi-Kin Lai; Yuying Chen; Zhengxi Zhang; Yun Liang; Hongmian Shui; Chen Li; Xiaoji Zhou (Physical Review Research)
The excited bands in optical lattices manifest an important tool for studying quantum simulation and many-body physics, making it crucial to measure high-band scattering dynamics under strong interactions. This work investigates both experimentally and theoretically the collisional scattering of ^{6}Li_{2} molecular Bose-Einstein condensate in the D band of a one-dimensional optical lattice, with interaction strength directly tunable via magnetic Feshbach resonance. We find a clear dependence of the D-band lifetimes on the interaction strength within the strongly interacting regime, which arises from the fact that the scattering cross section is proportional to the square of the scattering length. The maximum lifetime versus lattice depth is measured to reveal the effects of interactions. We also investigate the scattering channels of D-band molecules under different interaction levels and develop a reliable two-body scattering rate equation. This work provides insight into the interplay between interaction and the collisional scattering of high-band bosons in optical lattices, paving the way for research into strong correlation effects in high-band lattice systems.